1996
DOI: 10.1111/j.1432-1033.1996.t01-1-00516.x
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal Bisphosphorylated proenkephalin‐A‐(209–237)‐peptide from Adrenal Medullary Chromaffin Granules Possesses Antibacterial Activity

Abstract: The chromaffin granules have been shown to be an excellciit model to study the processing of proenkephalin-A and chromogranins. Recently, we reported a study dealing with the processing of chromogranin B/secretogranin 1 and the occurrence of the C-tertninal chromogranin B-derivcd peptide 614-626 which was shown to have antibacterial iictivity [Strub, J. M., Garcia-Sablonc, P., Looning, K., Taupenol, L., Hubert, P., Van Riochem. 229,. We also observed that this new antibacterial activity prcsent in chromaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 72 publications
2
55
1
1
Order By: Relevance
“…The results obtained by enzymatic digestion and mass spectrometry indicate that methionine at position 1 is the best candidate for oxidation. A similar posttranslational oxidation of methionine residues has been described for a fragment of proenkephalin A, a protein with antibacterial activity isolated from bovine chromaffin granules (36). Oxidation of gambicin but not of proenkephalin A influences antimicrobial activity.…”
Section: Discussionmentioning
confidence: 91%
“…The results obtained by enzymatic digestion and mass spectrometry indicate that methionine at position 1 is the best candidate for oxidation. A similar posttranslational oxidation of methionine residues has been described for a fragment of proenkephalin A, a protein with antibacterial activity isolated from bovine chromaffin granules (36). Oxidation of gambicin but not of proenkephalin A influences antimicrobial activity.…”
Section: Discussionmentioning
confidence: 91%
“…Relatively large amounts of pro-enkephalin-A and chromogranin-derived peptides are also found. MetzBoutique's group has shown in bovine that antibacterial activity is present within the intragranular chromaffin granule matrix and the extracellular medium following exocytosis [22][23][24][25]. These peptides inhibit the growth of Gram-positive bacteria (Micrococcus luteus and Bacillus megaterium) at micromolar concentrations.…”
Section: Anionic Peptidesmentioning
confidence: 99%
“…The use of these informations coming from invertebrates can be useful tools for treating septic diseases like Heart failure, the Crohn's disease or reactional arthritis [1][2][3][4][5][6]. Moreover, since these last 15 years, several antibacterial peptides have also been identified in mammals, particularly in secretions of immune cells or genital, digestive and intestinal epithelia tracts and skin of human [19][20][21] Secretory granules from adrenal medullary chromaffin cells contain a complex mixture of low molecular mass constituents, such as catecholamines, ascorbate, nucleotides, calcium and several water-soluble peptides and proteins [22][23][24][25]. These components are released into the circulation in response to splanchnic nerve stimulation.…”
Section: Anionic Peptidesmentioning
confidence: 99%
“…Since 1995, we have shown that antibacterial activities are present within the intragranular chromaffin granule matrix and are recovered in the extracellular medium following secretion. This activity has been assigned to chromogranin A and B fragments and PEAPs (4,(12)(13)(14)(15)(16)(17). Among the intragranular matrix components, enkelytin, an antibacterial peptide corresponding to the bisphosphorylated fragment PEAP209 -237, was identified (14).…”
mentioning
confidence: 99%
“…This activity has been assigned to chromogranin A and B fragments and PEAPs (4,(12)(13)(14)(15)(16)(17). Among the intragranular matrix components, enkelytin, an antibacterial peptide corresponding to the bisphosphorylated fragment PEAP209 -237, was identified (14). The antibacterial spectrum of enkelytin shows that this peptide is active in the micromolar range against several Gram-positive bacteria including Staphylococcus aureus, but it is not able to inhibit Gram-negative bacterial growth nor to lyse erythrocytes (15).…”
mentioning
confidence: 99%